Potential of biochar derived from three biomass wastes as an electrode catalyzing oxygen reduction reaction. Issue 1 (31st December 2022) - Zhang, Yue; Zhang, Juanqin; Song, Ke; Lv, Weiguang
ABSTRACT: Biochar is a porous carbonaceous material containing abundant redox functional groups and inorganic minerals, making it a potential electrode material. Nine electrodes were prepared with biochar produced from three different feedstocks at three pyrolysis temperatures, and their oxygen reduction reaction (ORR) activity and electrochemical impedance spectroscopy (EIS) were investigated. The results showed that all biochar electrodes had certain electrocatalytic activity as their current density ranged from 0.26 to 2.17 mA cm −2, half-wave potential at 0.24–0.41 V, electron transfer number at 2.1–3.9, Rct at 9.2–61.2 Ω, and Cdl at 1.1 × 10 −6 – 2.2 × 10 −4 F. For most biochar electrodes, the current density and half-wave potential increased as the pyrolysis temperature increased from 500°C to 700°C, which was closely related to the increase in aromatization degree (H/C) of biochar. Dairy manure biochar showed much lower current density and half-wave potential than sewage sludge biochar and wood chip biochar, probably due to its relatively smaller surface area. This study indicated that biochars could be converted to carbon electrodes, and both feedstock and pyrolysis temperature could influence the ORR activity of biochar electrodes.